ANALYSIS OF THE RAW NOODLE BUSINESS IN LOKTABAT UTARA VILLAGE, NORTH BANJARBARU DISTRICT - Amalia, Wina; Hasiani, Yarna; Zuraida, Ana (AL ULUM: JURNAL SAINS DAN TEKNOLOGI, 2024)
This study aims to examine the process of making raw noodles, analyze costs, revenues, profits, business feasibility, and the challenges faced during production. The research uses a case study method focused on the home industry business Widodo Food. Data collected includes both primary and secondary sources. The noodle-making process involves ingredient preparation, mixing, sheet formation, noodle cutting, rolling, and packaging. The results show the total cost of the raw noodle business is IDR 158,510,329 per month, with a production volume of 20,020 kg per month and a selling price of IDR 13,000 per kg. Consequently, the business generates a monthly revenue of IDR 260,260,000 and a profit of IDR 101,749,671. With an R/C Ratio of 1.64, the business is considered feasible. Challenges include damage to the roll press machine, power outages, and the lack of complete personal protective equipment (PPE) for employees.